The Utility of Transperineal Template Saturation Biopsy in the Detection of Clinically Significant Prostate Cancer - Kenta Onishi; Yasushi Nakai; Tatsuki Miyamoto; Fumisato Maesaka; Mitsuru Tomizawa; Takuto Shimizu; Shunta Hori; Daisuke Gotoh; Makito Miyake; Tetsuya Tachiiri; Nagaaki Marugami; Kiyohide Fujimoto; et al. (Advances in Urology)
Conclusions: Patients with a higher PI-RADS category tended to have csPCa. However, the PI-RADS category alone may not be sufficient for csPCa detection. TTSB detected csPCa in 10% of the patients with negative mpMRI findings. TTSB is a safe and crucial technique for accurately diagnosing prostate cancer.